LITERARY FOLKTALES PROMOTING CHILDREN'S MULTIPLE INTELLIGENCES/KARYA SASTRA YANG MENINGKATKAN KECERDASAN MULTIPEL ANAK-ANAK - Berhanu Asaye Agajie (Aksara, 2021)
AbstractThe objective of this study wasto investigate how literary folktale narrations promoting children's multiple intelligences. In this study qualitative design was adopted. The target populations of this study were found in Awi zone. In this case, expert sampling was used to capture multiple intelligences entrenched in a meticulous manifestation of knowledge in folktales.Through purposive sampling 20 folktale narrators (10 females and 10 male) were interviewed and two group discussions were conducted. The result of the study showed that engagement of children within literary narrations enablesthem to promote their linguistic, logical, spatial, musical, natural, interpersonal, intrapersonal, and bodily kinesthetic intelligences. Result and discussion showed thatliterary folktale narrations promote social cohesion regardless of age and gender. The children at any talent stage were acquainted with how to use their multiple intelligent through learning and their life experiences. This hypothesis is significant to elementary education because teachers able to observe more recurrently that students learn in different ways. Therefore, there is close relationship between literacy and folklore in influencing naturalist intelligencechildrento make a distinction among animals, categorize, and use features of the environment.Keywords: children, folktale, intelligences, literaryAbstrakTujuan penelitian ini adalah untuk meneliti bagaimana narasi folktale yang meningkatkan  kecerdasan multipel anak-anak. Dalam penelitian ini, digunakan desain kualitatif. Target populasi penelitian ini ditemukan di wilayah Awi. Dalam kasus ini, expert sampling digunakan untuk mengkaji kecerdasan multipel yang berakar dalam manifestasi pengetahuan folktale. Melalui purposive sampling(penyampelan berdasarkan tujuan), 20 pencerita folktale (10 perempuan dan 10 laki-laki) diwawancarai dan dua diskusi kelompok dilakukan. Hasil penelitian menunjukkan bahwa pelibatan anak-anak dalam narasi sastra memungkinkan mereka untuk meningkatkan kecerdasan linguistik, logis, spasial, musik, alami, interpersonal, dan kinestetik tubuh mereka. Hasil dan pembahasan ini menunjukkan bahwa narasi folktale meningkatkan hubungan sosial tanpa memandang usia dan jenis kelamin. Anak-anak pada setiap tahap bakat berkenalan dengan bagaimana menggunakan kecerdasan multipel mereka melalui pembelajaran dan pengalaman hidup mereka. Hipotesis ini sangat penting bagi pendidikan dasar guru dapat mengamati secara berulang-ulang bahwa siswa belajar dengan cara yang berbeda. Oleh karena itu, ada kaitan erat antara literasi dan cerita rakyat dalam memengaruhi kecerdasan alami anak-anak untuk membuat perbedaan di antara hewan, mengategorikannya, dan menggunakan karakteristik lingkungan.  Kata Kunci: anak-anak, dongeng, kecerdasan, literasi